Reconsidering a lightweight anonymous authentication protocol. (2nd January 2019) - Chen, Chien-Ming; Wang, King-Hang; Fang, Weicheng; Wu, Tsu-Yang; Wang, Eric Ke
ABSTRACT: In the cryptographic community, many efforts have been expended to build secure authentication protocols without using heavy asymmetric encryption. However, many of these efforts were ineffectual because many of them were found insecure due to low robustness to different types of attacks. This paper identifies a particular type of an attacker model that will never allow a secure lightweight authentication protocol. We demonstrate this finding by breaking a recently proposed protocol that is fixed from two insecure protocols. Then, we present the arguments for the impossibility of the existence of such a protocol while a secure protocol can appear only in an augmented version of this attacker model.